A Rare Vehicle-Assisted Ligature Hanging: Suicide at the Wheel. (March 2018) - Barranco, Rosario; Caputo, Fiorella; Bonsignore, Alessandro; Fraternali Orcioni, Giulio; Ventura, Francesco
Abstract : Abstract: Suicide by hanging inside a motor vehicle is a rare occurrence. A 48-year-old woman suffering from major depression was found having agonal breathing inside her automobile. A 20-mm diameter blue nylon rope was wrapped tightly around her neck, with its other end tied to a nearby wooden fence post. Despite resuscitation attempts, she was declared deceased after several minutes. The vehicle was located in an area with a slight downward slope. The motor was off. It was in neutral gear, with the parking brake disengaged. Consequently, the gravitational forces, attributable to the mass of the vehicle and the declivity of the terrain, caused the rope to tighten. The dynamics fulfill the criteria for a partial hanging, given the difference in height between the point at which the rope was secured to the post and woman's neck, which in turn presented the typical oblique upward groove. This case, thus, represents a unique mode of partial hanging inside a passenger vehicle, rarely reported in the literature. The relative lack of internal injury is also noteworthy, along with the fact that the victim was discovered while still alive. The latter feature can be explained by the absence of the sudden or violent acceleration forces that can be generated with the engine on.